It's showtime folks ; Doing more with less ; Real life : ADELA [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1992)
Features entertainers who became politicians. Their campaigns for the 1992 election with candidates Freddie Webb, Vicente Sotto III and Joseph Estrada. Tackles on the UP-PGH services ; Shows the Adela sugar workers stage play. Zarzuela about the life of sugarcane workers at Hacienda Adela at Silay Negros Occidental.
It's showtime folks (12 mins.) -- Doing more with less (13mins.) -- Real life : ADELA (14 mins.)
VHS.
Host, Cheche Lazaro, David Celdran.
Keywords: Philippine General Hospital; Entertainers -- Political activity. -- Philippines; Politicians -- Philippines; Sugar workers -- In literature. -- Philipines -- Silay Hawaiian Central (Negros Occidental); Sugar workers -- Social conditions. -- Philippines -- Silay Hawaiian Central (Negros Occidental, Philippines); Zarzuela